The Effects of External Magnetic Field on the Physical Properties of La0.41Ca0.59Mn1-xCuxO3 with x = 0.06 and 0.15 in the Temperature Range of 100 – 300 K - Y.E. Gunanto; W.A. Adi; B. Kurniawan; A. Purwanto; T. Ono; H. Tanaka; E. Steven (Atom Indonesia, 2019)
This work investigated the crystal structure, resistivity and specific heat of La0.41Ca0.59Mn1-xCuxO3  with x = 0.06 and 0.15. The samples were prepared by a solid reaction method and in milling with high energy milling (HEM) of 700 rpm for ten hours. Neutron scattering with high resolution powder diffraction (HRPD) is used to analyze the phase and crystal structure. For resistivity analysis, four point probes are used, and SQUID Quantum Design is used for specific heat analysis in temperatures range of 100 - 300 K. In all cases, the sample has an orthorhombic crystal structure with a space group Pnma. The influence of a magnetic field on the specific heat and resistivity is also determined as a function of temperature. The resistivity increases in the presence of an external magnetic field. At the temperature less than 184 K, the resisitivity follows the Arhenius model (ln R varies as 1/T0.25) while at higher temperatures it fits the metal-semiconductor model   (ln R varies as 1/T). The electronic specific heat parameter γ varies with magnetic field at x = 0.06, but not at x = 0.15.